2008
DOI: 10.1002/stc.239
|View full text |Cite
|
Sign up to set email alerts
|

Improved structural damage identification using random decrement signatures: Application to FEM data

Abstract: This article describes detection of structural damage using statistical properties of randomdec signatures. Proposed technique is model free and does not require input measurements. The technique is evaluated using acceleration data obtained from a finite element model of a frame-like structure. Damage in the model is represented by a structural member with nonlinear stiffness characteristic due to opening and closing cracks. The results suggest that reliability of damage detection would depend on the orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Theoretically, the ERD technique can only applied to deal with linear signals/damages, but it has been successfully extended for nonlinear systems by previous researches [17,18], and promising results have obtained from the numerical simulation early in this paper. Capabilities of identifying nonlinear damages of the proposed method are further investigated using a more complex and realistic structure.…”
Section: Test Descriptionmentioning
confidence: 91%
See 2 more Smart Citations
“…Theoretically, the ERD technique can only applied to deal with linear signals/damages, but it has been successfully extended for nonlinear systems by previous researches [17,18], and promising results have obtained from the numerical simulation early in this paper. Capabilities of identifying nonlinear damages of the proposed method are further investigated using a more complex and realistic structure.…”
Section: Test Descriptionmentioning
confidence: 91%
“…The original random decrement (RD) technique was introduced by Henry Cole in the early 1970s for estimating damping in aerospace structures [16]. Generally, given initial displacement, velocity, and random excitation, the "randomdec" signatures of the system can be extracted from the measured response x(t) using RD function δ(p) estimated as [17]:…”
Section: Extended Random Decrement Technique 21 Random Decrement Tecmentioning
confidence: 99%
See 1 more Smart Citation
“…. Shiryayev and Slater described detection of structural damage in the form of an opening up and closing cracks through random decrement signature technique. Another combined static–dynamic system identification study using measured damage signature and predicted damage signature is through the work of Wang et al .…”
Section: Previous Investigations On Damage Assessmentmentioning
confidence: 99%
“…In particular, the feature studied here represents the change in the mean values of the signatures obtained between neighboring degrees of freedom (DOFs). In previous work [18], this method has been applied to the data obtained from the finite-element model of a frame-like structure, where the damaged structural element was modeled as a beam with nonlinear stiffness characteristic. The study showed that the technique allowed detection of crack type damage even in the presence of significant additive noise in the measurement data.…”
Section: Introductionmentioning
confidence: 99%